Utilizing hiPSC-derived oligodendrocytes to study myelin pathophysiology in neuropsychiatric and neurodegenerative disorders. - Shim, Gina; Romero-Morales, Alejandra I.; Sripathy, Srinidhi R.; Maher, Brady J. (Frontiers in Cellular Neuroscience, 2024)
Oligodendrocytes play a crucial role in our central nervous system (CNS) by myelinating axons for faster action potential conduction, protecting axons from degeneration, structuring the position of ion channels, and providing nutrients to neurons. Oligodendrocyte dysfunction and/or dysmyelination can contribute to a range of neurodegenerative diseases and neuropsychiatric disorders such as Multiple Sclerosis (MS), Leukodystrophy (LD), Schizophrenia (SCZ), and Autism Spectrum Disorder (ASD). Common characteristics identified across these disorders were either an inability of oligodendrocytes to remyelinate after degeneration or defects in oligodendrocyte development and maturation. Unfortunately, the causal mechanisms of oligodendrocyte dysfunction are still uncertain, and therapeutic targets remain elusive. Many studies rely on the use of animal models to identify the molecular and cellular mechanisms behind these disorders, however, such studies face species-specific challenges and therefore lack translatability. The use of human induced pluripotent stem cells (hiPSCs) to model neurological diseases is becoming a powerful new tool, improving our understanding of pathophysiology and capacity to explore therapeutic targets. Here, we focus on the application of hiPSC-derived oligodendrocyte model systems to model disorders caused by oligodendrocyte dysregulation.